The Role of Public Relations in Maintaining Airline Image Amidst Schedule Delay Issues - Nova Gautami Putri (Sean Institute, 2025)
The term delay was first interpreted as a situation where the flight schedule is delayed to the point where the plane cannot depart or arrive at the scheduled time. The crisis of schedule delays that hit the airline industry is certainly a serious problem that must be resolved quickly and transparently, for that the airline appointed a public relations practitioner to resolve this situation so as not to cause losses to both parties. The purpose of this study is to determine the role of public relations in maintaining the image of the airline amidst the issue of schedule delays, then this research method uses qualitative studies to obtain results in the form of words or writings from people who have been observed, and the results of this study describe that, issues surrounding schedule delays have indeed been heard for a long time in the aviation world in any part of the world, the airline appointed a public relations practitioner to resolve this crisis by forming a team, compiling information, managing the media, and conveying it to the relevant parties. The role of public relations is required to work according to the norms of justice, convey information accurately and restore the name of the airline organization to be fragrant in the eyes of the public.